Theoretical prediction of a transient accumulation of nanoparticles at a well-defined distance from an electrified liquid–solid interface. Issue 41 (15th October 2018) - Chan, Crystal; Kätelhön, Enno; Compton, Richard G.
Abstract : On the basis of the Nernst–Planck equation, the Gouy–Chapman model, and an established model of near-wall hindered diffusion, this work predicts transient and highly-localised accumulations of nanoparticles at a well-defined distance from an electrified surface following a potential being applied. Abstract : The Brownian motion of nanoparticles near liquid–solid interfaces is at the heart of evolving technologies: recent developments in the sensing of nano-objects and energy storages based on electro-active colloidal solutions crucially rely on the understanding and, even more, on the control of particle transport near charged surfaces. On the basis of the Nernst–Planck equation, the Gouy–Chapman model, and an established model of near-wall hindered diffusion, this work predicts transient and highly-localised accumulations of nanoparticles at a well-defined distance from an electrified surface following a potential being applied. The interplay of electrostatics and near-wall hindered diffusion yields entirely unexpected effects: nanoobjects temporarily accumulate near the interface while even small electric potentials applied at the surface can dramatically enhance the mass transport of nano-objects towards it.